THE USE OF FORM-FOCUSED INSTRUCTION (FFI) ON STUDENTS ABILITY TO WRITE A BIOGRAPHICAL RECOUNT TEXT - Andriyani, Aan; Vonti, Lungguh Halira; Sutisna, Entis (Journal of English Teaching and Linguistics Studies (JET Li), 2020)
Writing is one of the language skills that should be mastered by students. However, the skill is not easy to be grasped since students are not only demanded to generate ideas, but they also should understand how the written language constructed by using appropriate words, tenses, and the construction of the text itself. Thus, the teacher should facilitate students to develop their writing ability. Form-Focused Instruction (FFI) was chosen as an approach that can be applied on teaching writing. This research was conducted to investigate the effect of Form-Focused Instruction (FFI) on students ability to write a biographical recount text. The population of this research was tenth grade students of SMA Negeri 8 Kabupaten Tangerang. 36 students of class X MIA 2 were the sample used in this research by using random sampling technique. Pre-experimental method with one group pre-test post-test design was applied in conducting this research. The instrument of this research was writing test which was given to measure students writing ability. The data were gained from the pre-test and post-test. The data were analyzed by using t-test formula. From the calculation, it was found that the t-test value is 14.84 when was higher than the t-table value (2.03). Therefore, the null hypothesis (Ho) is rejected and alternative hypothesis (Ha) is accepted. Thus, it can be concluded that the use of Form-Focused Instruction (FFI) affected students ability to write a biographical recount text.